Relationship of Oral Pathologies Associated with Second Molars to the Patterns of Adjacent Impacted Third Molar - Hira Butt, Maria Jabbar, Dur e Shumyle, Zahra Moeen, Samra Liaqat, Fareeha Irum, Nauman Rauf Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To assess the relationship of oral pathologies associated with second molars to the patterns of adjacent impacted third molar. Methodology: A cross sectional descriptive study was conducted on 385 Orthopantomograms (OPG) of patients. The study was conducted in the Institute of Dentistry, CMH Lahore Medical College, Lahore, Sharif Medical and Dental College (SMDC) and Services Institute of Medical Sciences (SIMS) over a period of three months from December 2020 to February 2021. The Pell and Gregory classification was used for depth of third molar impaction and ramus relationship of mandibular third molars. Winter`s classification was used for classifying the angle of impaction. Results: The association between presence of caries (p=≤0.001) and external resorption (p=≤0.001) in second mandibular molar with depth of impaction of adjacent an impacted third molar, ramus relationship of third molar with presence of external root resorption in second molar (p=≤0.001) and presence of caries (p=0.005), periapical radiolucencies (p=0.009) and external root resorption (p=≤0.001) in second molar with the angle of impacted third molar were significant. The association of presence of caries, pericoronal, periapical radiolucencies and external root resorption in the maxillary second molars with the depth and angle of adjacent impacted third molars was not significant. Conclusion: The carious lesions were the highest where the third molar had class A depth of impaction while the maximum external resorption was seen where the third molar had class C depth of impaction. Second mandibular molars adjacent to impacted third molars in class 2 ramus relationship had the most external root resorption. It was seen that second molars adjacent to the impacted third molars with mesioangular impactions had the highest percentage of caries and periapical radiolucencies while those adjacent to third molars with horizontal angle of impaction showed the maximum external root resorption.